Meningkatkan Keterampilan Berbahasa Secara Produktif melalui Metode Task-Based Instruction - Toteng Suhara (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2023)
This research was motivated by the low language skills of Class X MIPA 2 students at SMAN 8 Bandung. The research objective was to improve the learning outcomes of productive language skills for class X MIPA 2 students at SMAN 8 Bandung in the 2020/2021 academic year through the Task-based Instruction method with the help of newspapers. The method used in this research is Classroom Action research, which consists of three cycles. The stages of each cycle include planning, implementing, observing, and reflecting. Analysis of the data used in this study using descriptive and qualitative analysis techniques The results showed that there was an increase in the learning outcomes of productive language skills with each cycle. In cycle I, the average student learning outcomes were 60.27 from KKM 70, with a completeness percentage of 16%. In cycle II, the average student learning outcomes increased to 69.44, with a mastery percentage of 72%. In cycle III, the average student learning outcomes increased to 81.93%, with a completeness percentage of 100%. This data shows that the Task-Based Instruction method can improve language skills learning outcomes productively.